An atomic-scale approach for biodiesel boundary lubricity characterisation. (September 2016) - Chong, W.W.F.; Ng, J.-H.
Abstract: Biodiesel lubricity is generally characterised through the wear scar diameter produced using high frequency reciprocating rig (HFRR). More recently, the adequacy of Stribeck curve in characterising biodiesel lubricity is also being investigated. However, for a rough surface contact, asperity interactions at nano-scale are predominantly the root cause for excessive friction along boundary and mixed lubrication regimes that could eventually lead to material wear. Mitigation of this frictional loss depends heavily on the formation of boundary-adsorbed tribo-film, which is a consequence of molecular chemical reaction with the surface. It is therefore critical to characterise the lubricity of biodiesel with respect to its frictional behaviour at asperity level. Using Lateral Force Microscopy (LFM), the study examines the boundary frictional characteristics for various biodiesels derived from coconut, palm, olive, canola and soybean at different applied loads and sliding velocities on an ultra-smooth surface. Interpreting the measured boundary friction using the modified Eyring thermal activation energy approach, the study found that for a more effective boundary lubrication using vegetable oil derived biodiesel, a sufficient load carrying capacity and low shear characteristics could be achieved by having a good balance between the saturated-unsaturated and monounsaturated-polyunsaturated fatty acid methyl ester content, such as palm methyl ester. Highlights: Formation of boundary-adsorbed film mitigates boundary friction. Lateral Force Microscopy is used to examine biodiesel lubricity along smooth surfaces. Thermal activation energy approach is used to interpret the measured friction force. Effective boundary lubrication needs load carrying capacity with low shear behaviour. Good biodiesel lubricity is attained with a balanced fatty acid methyl ester content.